A Healthy Retirement Program for Thai government teachers: a quasi-experimental and comparison groups study - Numporn Insin; Chanuantong Tanasugarn; Sarunya Benjakul (College of Public Health Sciences, Chulalongkorn University, 2022)
Purpose - The purpose of this study is to evaluate the Healthy Retirement Program's effectiveness toward skills improvement and evaluate changes in subjective health. Design/methodology/approach - A quasi-experimental, pre and posttest of the comparison groups was conducted. Teachers who were going to retire within one year were recruited into the experimental (n = 47) and the comparison groups (n = 43). Questionnaires were administered at baseline, posttest and at the 6-months follow-up. An independent t-test and Mann-Whitney U test were applied to determine the differences in outcomes between groups. Findings - The results revealed different effects regarding teachers' health status. In those who had no chronic disease, the experimental group had higher skills to understand health information at posttest and at follow-up (p = 0.036, 0.028). Skills to apply health information was also greater at follow-up (p = 0.042). Among those suffering from a chronic disease, skills to access and apply health information were significantly higher in the experimental group than that of the comparison at follow-up (p = 0.011, 0.046). Greater perceived health of the experimental group was also indicated (p = 0.032). Originality/value - While the health conditions of teachers at the preretirement period are inconsistent, healthy lifestyle management after retirement is a crucial skill for retirement adjustment. Supporting teachers to be health literate should be included in the retirement planning program which emphasizes preretiree's ability to understand and take control of their health.